Income Contribution of Housewives as Workers in the Ant Palm Sugar Industry Kontribusi Pendapatan Ibu Rumah Tangga Sebagai Pekerja Industri Gula Semut Sari Aren - Sulistiawati, Mayasari (Agribisnis Fakultas Pertanian Universitas Islam Makassar, 2023)
Income Contribution of Housewives as Workers in the Ant Sari Palm Sugar Industry in Rejang Lebong Regency, aims to find out the family income of housewives as workers in the Ant Sari Palm Sugar Industry and to find out how much the contribution of housewives as workers in the Ant Sugar Industry palm juice. This research was carried out in July 2023 in Air Meles Atas Village, Selupu Rejang District, with the consideration that there had been no previous research in this area regarding